Managing Instructional Planning in Nursing Education: Development and Implementation of a Learning Management Model - Jolie Febri Ponamon; Harol R. Lumapow; Deitje A. Katuuk; Jeffry Sony Junus Lengkong (International Journal of Information Technology and Education, 2026)
This study aims to analyze and develop a learning planning management model at the Faculty of Nursing, Sariputra Indonesia University, Tomohon, within the framework of the AIPNI competency-based curriculum. The study used a qualitative approach with an instrumental case study design to deeply understand the learning planning process involving study programs, lecturers, faculty leaders, and the internal quality assurance unit. Data were collected through interviews, observation, and documentation, then analyzed thematically with reference to the POAC (planning, organizing, actuating, controlling) management function. The results showed that learning planning has been implemented systematically through the preparation of Semester Learning Plans (RPS), academic coordination meetings, integration of theory and clinical practice, and periodic monitoring and evaluation. These practices reflect the application of the principle of constructive alignment that emphasizes the alignment between learning outcomes, learning strategies, and assessments. The integration of theoretical, laboratory, and clinical practice learning has been proven to strengthen the development of student competencies and clinical reasoning. However, the effectiveness of planning is still influenced by limited lecturer resources, a high student ratio, and the availability of practice facilities. This study offers a learning planning management model based on management functions integrated with an internal quality assurance system as a conceptual contribution to strengthening nursing education governance. Practically, these findings provide implications for nursing educational institutions in improving the quality of learning planning systematically, contextually, and sustainably to produce competent graduates who are relevant to the needs of the healthcare system.